Beginning teachers’ professional development in Germany, Singapore, China, and Kazakhstan - Oxana Kereyeva; Almazhai Yegenissova; Adem Bayar; Kairat Tleuov; Nurbike Bisaliyeva; Karylgash Kudarova; Shynar Iskakova (Institute of Advanced Engineering and Science, 2026)
This study explores the challenges faced by beginning teachers in Kazakhstan due to inadequate professional development (PD) support, leading to high attrition rates and adaptation difficulties. A comparative analysis of PD programs in Germany, Singapore, China, and Kazakhstan identifies best practices that enhance teacher retention, professional growth, and teaching quality. Employing Bereday’s four-phase comparative methodology, this study systematically reviews approximately 20 policy documents and research articles from the selected countries. The findings indicate that effective PD programs incorporate structured mentoring, professional learning communities (PLCs), and action research. In contrast, Kazakhstan’s limited PD framework, characterized by brief mentoring periods and heavy teacher workloads hinders continuous professional growth. This study recommends extending the mentoring program to two years, reducing workloads, and integrating structured PD activities such as peer observations, subject-specific discussions, and collaborative workshops. Additionally, fostering professional communities and administrative support can ease the adaptation process, ultimately improving teacher retention and education quality. These recommendations provide a foundation for enhancing Kazakhstan’s PD system, aligning it with international best practices to establish a sustainable support structure for beginning teachers.